2010
DOI: 10.1103/physrevlett.104.157404
|View full text |Cite
|
Sign up to set email alerts
|

Transient Fluorescence of the Off State in Blinking CdSe/CdS/ZnS Semiconductor Nanocrystals Is Not Governed by Auger Recombination

Abstract: The observed intermittent light emission from colloidal semiconductor nanocrystals has long been associated with Auger recombination assisted quenching. We test this view by observing transient emission dynamics of CdSe/CdS/ZnS semiconductor nanocrystals using time-resolved photon counting. The size and intensity dependence of the observed decay dynamics seem inconsistent with those expected from Auger processes. Rather, the data suggest that in the "off" state the quantum dot cycles in a three-step process: p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
164
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(181 citation statements)
references
References 22 publications
17
164
0
Order By: Relevance
“…As an extension of this framework, multiply charged states were suggested in order to account for a dark-state quantum yield much lower than its biexcitonic counterpart. 29 Multiply charged states are also consistent with the distribution of lifetimes in the dark state 38 as well as the present findings on the distribution of dark intensity states. The wide distribution of bright intensity states reported in this paper could be due to an alternative mechanism of fluctuating non-radiative channels.…”
Section: Implications Of the Distributed States On Models Of Blinkingsupporting
confidence: 77%
See 1 more Smart Citation
“…As an extension of this framework, multiply charged states were suggested in order to account for a dark-state quantum yield much lower than its biexcitonic counterpart. 29 Multiply charged states are also consistent with the distribution of lifetimes in the dark state 38 as well as the present findings on the distribution of dark intensity states. The wide distribution of bright intensity states reported in this paper could be due to an alternative mechanism of fluctuating non-radiative channels.…”
Section: Implications Of the Distributed States On Models Of Blinkingsupporting
confidence: 77%
“…Indeed, the present findings contribute to the growing body of evidence supporting a multi-state picture of blinking. 3, 13, 32, 37-39 Emission lifetime measurements in CdSe/ZnS QDs have demonstrated that the off state can be further resolved into a manifold of states 38,39 which is consistent with the evidence indicating a distribution of dark intensity states (Fig. 2).…”
Section: Implications Of the Distributed States On Models Of Blinkingsupporting
confidence: 69%
“…Furthermore, we have shown that both trion charge states and concomitantly their charged biexcitons have high luminescence quantum yields, contrary to observations at room temperature 25 , indicating that Auger recombination is inefficient in these materials. Thus the photo-charging mechanism of our NCs can be attributed to a tunnelling process, which has significant implications for alternative photoluminescenceblinking mechanisms 41,42 . Another interesting consequence of NC engineering is revealed in the g-factor measurements.…”
Section: Discussionmentioning
confidence: 99%
“…However, charging of NCs can promote Auger recombination and trap states can bind charge Colloidal lead halide perovskite nanocrystals H Huang et al carriers, preventing recombination, all of which has been considered to contribute to blinking. [102][103][104] Tian et al 98 observed PL blinking from MAPbI 3 nanorods (Figures 8h-j) and attributed it to photo-induced activation and de-activation of PL quenching sites, presumably present at the ends of the rods where formation of geometrical and chemical defects are most likely to occur. Similarly, blinking was also observed in single perovskite MAPbBr 3 NCs and attributed to the presence of charge trapping surface states.…”
Section: Quantum Confinement In Perovskite Ncsmentioning
confidence: 99%